2017
DOI: 10.1089/neu.2016.4602
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Penetrating Ballistic-Like Brain Injury Induced Cognitive Deficits after Neuronal Differentiation of Transplanted Human Neural Stem Cells

Abstract: Penetrating traumatic brain injury (PTBI) is one of the major cause of death and disability worldwide. Previous studies with penetrating ballistic-like brain injury (PBBI), a PTBI rat model revealed widespread perilesional neurodegeneration, similar to that seen in humans following gunshot wound to the head, which is unmitigated by any available therapies to date. Therefore, we evaluated human neural stem cell (hNSC) engraftment to putatively exploit the potential of cell therapy that has been seen in other ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…In animal studies of SCI, traumatic brain injury, and ischemic stroke, implantation of NSI‐566 during acute or subacute period has consistently produced cavity‐filling tissue by the cells . Still, it is surprising that such cavity‐filling effect is observed in a human brain tissue lesioned 2 years prior to the cell implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies of SCI, traumatic brain injury, and ischemic stroke, implantation of NSI‐566 during acute or subacute period has consistently produced cavity‐filling tissue by the cells . Still, it is surprising that such cavity‐filling effect is observed in a human brain tissue lesioned 2 years prior to the cell implantation.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that after transplantation into the injured brain following TBI, these cells can survive for a long period and become region-specific functional cells [92]. Transplantation of the adult-generated NSCs in mouse TBI models has shown improvements of learning deficits [93, 94]. …”
Section: Exogenous Stem Cells Via Neural Transplantation For Post-tbimentioning
confidence: 99%
“…The destructive ravages of externally-or internally-induced damage to the brain and CNS trauma, whether this be of mild, moderate or severe extent, will invariably be the consequence of proximal-distal causation, proliferation and severity [1][2][3], such as cerebral ischemia which afflicts millions of individuals worldwide with eventual survivors suffering from long-term functional and cognitive deficits. Cerebral damage in traumatic brain injury (TBI) may be accompanied by headache, of varying intensities and localizations, dizziness and illfeeling, loss of consciousness, blurring of vision, hearing impediments, confusion states, loss of memory and cognitive capacity, seizure activity, paralysis and coma as the primary-registered symptoms and expressions, with the expectation of accompanying damage to bloodbrain-barrier integrity, accelerated apoptosis and excitotoxicity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%